The association between ea tfng habits and physical activity with depression among school-going adolescents in Kelantan - Kamarulzaman, Erliza Nur Md (Universiti Sains Malaysia, 2016)
Poor eating habits and lack physical activity are lifestyle factors which are linked to the aetiology of depression among adolescents suggesting that improvement of diet and physical activity may be beneficial for the mental health of the adolescents since the prevalence for depression among the adolescents are on the rise. Therefore, this study determines the association between eating habits and physical activity with depression among school-going adolescents in Kelantan. This study is a cross-sectional study involving respondents from five secondary schools in Kelantan, age 13 to l 6 (n=250) from Febmary to March 20 l 6 using self-administered questionnaire and anthropomettic measurement. The Eating Behaviour Questionnaire (EBQ) was used to assess the eating habits of the study respondents. Physical activity level and depression level was assessed using Physical Activity Questionnaire for Adolescents (PAQ-A) and Depression, Anxiety and Stress (21-items) (DASS-21) respectively. Majority of the respondents were in the normal weight status category (69.2%). 80.4% of the study respondents skipped at least one meal in a day and meal skippers were especially widespread among the female respondents (86. l %). The most commonly skipped meal was breakfast (54.4%), followed by dinner (52.8%), and lunch (35.2%). Eating outside, eating takeaway food and at fast food restaurants were generally uncommon among study respondents. In respond to dietary practices, majority of them claimed to be not choosy and eat whatever food that was available to them (29.6%) and prefers eating fruits and vegetable (26.3%). Very few of the respondents had restricted dietary fats, sugar and red meat. 54.6% of the respondents were categorized as having low physical activity level, another 41.8% were categorized as having moderate physical activity level and only 3.6% of the study respondents demonstrated as having high physical activity level. Low physical activity level was especially prevalent among female respondents, at 70.6%. The prevalence of depression, anxiety and stress among study respondents were 67%, 52.8% and 80.2% respectively. Significant associations were observed between depression level with meal skippers and lunch skippers, at x2=4.598; p=0.032 and x2=12.283; p < 0.001 respectively. No other significant associations were observed for other eating habits variables. No significant association was also observed between physical activity and depression level. Data from the current study showed that meal skipping is a factor associated with depression among adolescents, particularly in female. Hence, recognizing the importance of proper routine of meal intakes for the betterment of mental health. Furthermore, findings from this study showed that anxiety is more prevalent followed by depression and stress respectively implying the need to explore the relationship between eating habits and physical activity with anxiety among adolescents in future study.